Di- and tetracyano-substituted pyrene-fused pyrazaacenes: aggregation in the solid state - Ueberricke, Lucas; Ciubotaru, Ioana; Ghalami, Farhad; Mildner, Felix; Rominger, Frank; Elstner, Marcus; Mastalerz, Michael (Chemistry - a European journal, 2020)
Five di- and tetracyano-substituted pyrene-fused pyrazaacenes were synthesized and studied as potential electron acceptors in the solid state. Single crystals of all compounds were grown and the crystal packing studied by DFT calculations (transfer integrals and reorganization energies) to get insight into possible use for semiconducting charge transport.
Gesehen am 05.10.2020